Klausula Pembatasan dan Pengalihan Tanggung Jawab Pialang Berjangka dalam Kontrak Baku Pemberian Amanat secara Elektronik On-Line - Siti Anisah; Catur Septiana Rakhmawati (Jurnal Hukum IUS QUIA IUSTUM, 2017)
The core problems in this study include first, why the clause of liability limitation is regulated in the Regulation of Bappeti Head No. 107/BAPPEBTI/PER/11/2013 which should provide protection to the parties as the futures trading actors? Second, is the standard contract in the attachment of Regulation of Bappebti Chief No. 107/BAPPEBTI/PER/11/2013 is a binding contract for the traders in the Commodity Futures Trading? This is a normative legal research and its results showed first, the attachment of Regulation of Bappeti Head No. 172/BAPPEBTI/PER/11/2013 is a form of government intervention into the contractual relationship, containing the clause  of the liability limitation of one of the parties namely Broker. This regulation gives injustice for investors. Second, this contract should be null and the mechanism of its cancelation is through judicial review to the Supreme Court.